Pengaruh Faktor Sosial Dan Perilaku Konsumen Terhadap Keputusan Boikot Produk Pro Israel: Studi Kasus Pada Generasi Z Di Kota Kisaran - Wahyuni, Sri; Khulsum, Umi; Fadila, Zahra Nur; Apriliani, Lilis; Sahla, Hilmiatus (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
In this era of globalization, social and political issues are increasingly influencing consumer behavior, especially among the younger generation or known as Generation Z. One of the issues that has received great attention from the world is the Palestinian conflict with Israel. The purpose of this study is to determine the effect of social factors and consumer behavior on the decision to boycott pro-Israel products, both partially and simultaneously. This study used 119 respondents as a research sample taken using a quantitative approach analysis method technique based on descriptive research methods. The results of the study based on the simultaneous test (F test) show that simultaneously (simultaneously) social factors and consumer behavior have a positive and significant effect on the decision to boycott pro-Israel products in Kisaran City. The results of partial hypothesis testing (t test) show that social factors and consumer behavior partially have a positive and significant effect on the decision to boycott pro-Israel products in Kisaran City. Based on the results of the determination test, it is known that consumer decisions can be explained by social factors and consumer behavior by 61.7%, while the remaining 38.3% is explained by other variables not examined in this study.